Aphasia and Acquired Reading Impairments: What Are the High-Tech Alternatives to Compensate for Reading Deficits? - Cistola, Giorgia; Farrús, Mireia; van der Meulen, Ineke (International journal of language & communication disorders, 2021)
Background: People with aphasia (PWA) frequently present impairments in reading comprehension. Such impairments can be particularly debilitating due to the limitations and constraints they impose on everyday life. Recent technological advancements in the field of information and communication technologies offer many compensative tools for PWA. However, most technological tools are designed for patients with speech production impairments. Instruments addressing reading impairments associated with aphasia remain scarce and underrepresented in the scientific literature. Aims: To conduct a state-of-the-art review of the technologies currently available to PWA and acquired reading impairments. In particular, this review covers (1) research on technologies explicitly developed to compensate for reading difficulties associated with aphasia; and (2) research into which accessibility features included in mainstream high-tech systems are helpful for PWA when trying to access written material. Methods & Procedures: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) international standard, the authors conducted a systematic review from 2009 to 2019. The databases inspected were Scopus, Web of Science, PubMed, the Cochrane collection, IEEE Xplore, ScienceDirect and SpringerLink. Other research papers were included after checking the references of the selected papers. Main Contribution: The review reveals that research on compensative devices for reading impairments largely neglects tools for individuals with aphasia and acquired reading difficulties. Most of the studies in this field are qualitative investigations of how patients with literacy difficulties tackle everyday tasks with the help of mainstream technology (e.g., smartphone applications). Therefore, this paper highlights the scarce high-tech alternatives that support text comprehension in PWA and acquired reading impairments, and suggests further work on the development of customized software for smartphones and personal computers. Conclusions: High-tech reading tools may help PWA to regain reading autonomy. PWA and acquired reading impairments employ a wide array of devices to overcome reading difficulties, which underlines the importance of reading in everyday life. However, the supports currently available are not yet flexible and accurate enough to answer their day-to-day needs. Thus, further work is necessary to enhance the compensative devices available to them. For instance, existing new technologies in the area of natural language processing (such as automatic text simplification) could potentially be used in compensative devices.